PRAGMATIC AND STYLISTIC FEATURES OF LEXICAL-PHRASEOLOGICAL HOMONYMS - Nurullayeva Shirinabonu Ne'matullayevna (International Journal of Literature and Language Studies, 2026)
This article studies the pragmatic and stylistic properties of lexical and phraseological homonyms in modern linguistics. It analyzes the nature of homonymy between lexical units and phraseological units, identifies their functional properties in various speech situations. Particular attention is paid to the pragmatic aspect associated with the contextual connection of meaning and the speaker's communicative intentions, as well as the stylistic role of homonyms in creating expressiveness, polysemy, and verbal expressiveness. The study shows that lexical and phraseological homonyms are an important means of artistic expression and language play.